The Role of Social Service in Confronting Recidivism to Drug Abuse - Jasim, Sabreen Hussein; Abdullah, Zainab (Al-Adab Journal, 2021)
The research dealt with the role of social service in confronting the problem of addiction and drug abuse and preventing it using various technical methods, and mitigating the effects of drugs abuse, showing the treatment stages for social service and the basic goals, social service practices for returning to addicts, and methods of preventing relapse. The social service profession plays an important role in the process of rehabilitation of addicts, and this role is no less important than the therapeutic role, rather it is part of it, and the rehabilitation role is part of the integrated treatment plan for work in the field of addiction, and this part is called aftercare. It is concerned with establishing facts about the conditions and aspirations of returnees when planning programs for their care. It identifies their preferences and studies their needs, and makes them a material for plans.